A comparative study of spectral and temperature sensing properties of Er3+ mono-doped LnNbO4 (Ln = Lu, Y, Gd) phosphors under 980 and 1500 nm excitations. (March 2019) - Wang, Xin; Li, Xiangping; Xu, Sai; Cheng, Lihong; Sun, Jiashi; Zhang, Jinsu; Li, Lei; Chen, Baojiu
Graphical abstract: The temperature sensing properties for LnNbO4 :Er 3+ are independent from excitation wavelength and LuNbO4 : Er 3+ sample has the highest temperature sensing sensitivity and the maximum sensitivity is 0.0058 K −1 . Highlights: Luminescence properties of LnNbO4: Er3+ was compared. UC luminescence mechanism is independent from Ln. LuNbO4: Er3+ presents stronger UC emission than others. Temperature sensing is independent from excitation wavelength. LuNbO4: Er3+ shows best temperature sensitivity. Abstract: LnNbO4 :Er 3+ (Ln = Lu, Y, Gd) phosphors were prepared through a conventional solid-state reaction method. The phase purity of the samples was characterized by X-ray diffraction (XRD). A comparative study of spectral and temperature sensing properties of LnNbO4 :Er 3+ (Ln = Lu, Y, Gd) phosphors was presented. The excitation spectra of the samples show a strong band in the region of 200–350 nm coming from the NbO4 4−, thus indicating efficient energy transfer from the host to Er 3+ . From the dependence of upconversion (UC) luminescence spectra on laser diode working current, it was confirmed that 2- and 3-photon processes were respectively responsible for both the green and the red UC emissions under 980 and 1550 nm excitations. The temperature sensing properties for LnNbO4 :Er 3+ were compared under individual excitation of 980 and 1550 nm. It was found that the temperature sensing was independent from the excitation wavelength, but LuNbO4 :Er 3+ phosphors yielded the highest luminescence intensity and maximum temperature sensitivity.